ETIKA PROFESI ADVOKAT DALAM PERSPEKTIF PROFESIONALISME PENEGAKAN HUKUM - Sunarjo Sunarjo (University of Merdeka Malang, 2017)
Profession ethics was a dimensional concept, not only in perspective philosophy that became a principle ofmethodical and systematical elaboration about norm and value which provided the basis of human act. Ethicsas a normative science was dealing with norm or value which decided to evaluate someone whether (s) he is agood or bad human. Profession as a lawyer adhered to someone after doing some steps: having a title as masterof law, joining Training Special for Lawyer Profession (PKPA), passing the examination of Lawyer Professiontest (UPA), being an apprentice at least 2 years in a lawyer office, and being inaugurated in an open or publiccourt in an appellate court. The realization of noble profession (Officium Nobile) was that every lawyer inimplementing their professions had to obey to the profession ethics (code of ethics) and regulation of legislation.One of the most important things was fully obeying the lawyer oath. The thesis was when every lawyerobeyed the three things and it would have good effect for the lawyer and also for the clients and for the nationtoo.